Pneumothorax secondary to a Pulmonary Bullae in a dog - Picelli, Julia Perinotto; de Sá, Simone Scarpin; Rosado, Isabel Rodrigues; Teodoro, Ananda Neves; Lima, Ana Julia de Souza; Kiellander, Barbara Monteiro; Serakides, Rogéria; Alves, EndrigoGabellini Leonel (Acta Scientiae Veterinariae, 2022)
Background: Pulmonary bullae are thin-walled cavitary lesions within the subpleural parenchyma. They are a result of the destruction, dilatation and coalescence of bordering alveoli and their rupture is the most common cause of pneumothorax in dogs. Radiographic and CT imaging are excellent tools for identifying and quantifying pneumothorax. Surgical treatment is considered standard for treatment of pneumothorax consequential to pulmonary bullae. The aim of this report was to describe a case of pneumothorax secondary to pulmonary bullae in a dog. Case: A 5-year-old male crossbreed dog, weighing 11.5 kg, was presented to the Uberaba’s Veterinary Hospital due to becoming easily tired in the previous 3 weeks, and its worsening in the last 2 days by presenting panting. The dog’s guardian did not witness any traumas, but informed that the animal resided with other 14 dogs and also that it frequently collided the thorax against the door when it came down from the bed. Physical examination showed diaphragmatic breathing, inspiratory dyspnea and stridor lung sound. Thoracocentesis revealed presence of air in the pleural cavity and pneumothorax. Radiographic images confirmed this condition. The dog stayed in the hospital and chest drains were placed. Since the amount of sucked air did not reduce with time and due to the emergence of subcutaneous emphysema, the dog went through exploratory thoracotomy that revealed impairment of the right caudal lung lobe, proceeding to lobectomy. The dog stayed in the hospital with chest drains until the contents of the suctions reduced significantly. With the removal of the drains, the dog was sent home and had a full recovery. Histopathology of the impaired lung revealed pulmonary bullae. Discussion: The dog from this report presented clinical signs consistent with pneumothorax, such as dyspnea, diaphragmatic breathing and exercise intolerance. Radiography of the chest region revealed images consistent with this condition, as it is an excellent tool for identifying it. This dog’s guardian was unable to confirm if there was occurrence of trauma due to the large number of cohabitants. In dogs, spontaneous pneumothorax commonly results from the rupture of pulmonary bullae, and these bullae may result from trauma, infectious diseases, thrombosis, obstructive, neoplastic, congenital or idiopathic conditions. Except from trauma, there were no evidence to support any of the other causes of pulmonary bullae in this case. Traumatic injuries are very common in veterinary medicine, and blunt thoracic traumas with consequential pneumothorax are especially common. The emerging of subcutaneous emphysema, as happened with this dog, is frequently associated with pneumomediastine, and rarely has pathophysiologic impairments. The patient stayed in the hospital for support therapy and thoracocentesis, corroborating with literature; but since there was no improvement, it went through exploratory lobectomy, which revealed impairment of the right caudal lung lobe, proceeding to its exeresis. Surgical intervention is standard procedure in these cases. Histopathology of the impaired lung suggested the presence of pulmonary bullae. In literature, histopathological definitions for this condition are inconsistent, but usually locate the bullae within the pulmonary parenchyma, having walls less than 1 mm thick. Through radiology, unlike with cysts, identifying pulmonary bullae is challenging. In conclusion, this report showed that pulmonary bullae should be considered as a differential diagnose in patients showing pneumothorax considering it is hard to identify through imaging, and that it is important to adopt early therapy and surgical intervention for better outcomes. Keywords: dyspnea, panting, pulmonary lobectomy, thoracotomy, chest drain. Titulo: Pneumotórax secundário a bolha pulmonar em cão. Descritores: dispneia, ofegante, lobectomia pulmonar, toracotomia, dreno torácico.